Hubungan pengetahuan perawat tentang australian triage scale terhadap response time pasien - Kartikasari, Ellysa August; Faozi, Ekan (Holistik Jurnal Kesehatan, 2025)
Background: Delays in handling or response time of patients in the Emergency Department will have a negative impact on the patient's condition. Factors that influence the success rate of implementing emergency measures, such as the number of health workers and health facilities, patient inflow, family perspectives on care and the level of nurses' knowledge about implementing triage. Purpose: To determine the relationship between nurses' knowledge of the Australian Triage Scale and patient response time. Method: This study uses a quantitative correlational method with a cross-sectional approach. Sampling using a non-probability sampling method with a total sampling approach and the number of respondents was 29 people. The study was conducted in November 2024 at the Emergency Room of the Ir. Soekarno Sukoharjo Regional General Hospital. The instruments used were the Australian Triage Scale knowledge questionnaire and a response time measuring instrument in the form of a stopwatch. Univariate and bivariate data analysis was carried out using the Spearman's Rank statistical test. Results: Bivariate analysis with Spearman's Rank statistical test obtained a p value of 0.002 (<0.05), indicating that Ho was rejected and it can be interpreted that there is a relationship between the level of nurses' knowledge of the Australian Triage Scale and patient response time. Conclusion: The level of nurses' knowledge about the Australian Triage Scale is included in the sufficient category. While the response time is included in the fast category. The results of the Spearman's Rank statistical test obtained a significance value (p-value) of 0.002, so there is a significant relationship between the level of nurses' knowledge about the Australian Triage Scale and patient response time.   Keywords: Australian Triage Scale; Emergency Department; Knowledge; Nurses; Response Time.   Pendahuluan: Keterlambatan penanganan atau response time pada pasien yang ada pada Instalasi Gawat Darurat (IGD) akan berdampak buruk pada kondisi pasien. Faktor-faktor yang memengaruhi tingkat keberhasilan dalam mengimplementasikan tindakan gawat darurat, seperti jumlah tenaga kesehatan dan sarana kesehatan, arus masuk pasien, perspektif keluarga terhadap perawatan serta tingkat pengetahuan perawat tentang pengimplementasian triase. Tujuan: Untuk mengetahui hubungan pengetahuan perawat tentang australian triage scale terhadap response time pasien. Metode: Kuantitatif korelasional menggunakan pendekatan cross-sectional. Dalam mengambil sampel diterapkan metode non-probability sampling yang menggunakan pendekatan total sampling dan total sebanyak 29 responden. Penelitian dilaksanakan pada bulan November 2024 di IGD RSUD Ir. Soekarno Sukoharjo. Instrumen yang digunakan yaitu kuesioner pengetahuan Australian Triage Scale dan untuk pengukuran response time menggunakan stopwatch.  Analisis data univariat dan bivariat dengan mengaplikasikan uji statistik Spearman’s Rank. Hasil: Analisis bivariat dengan uji statistik Spearman’s Rank didapatkan p-value 0.002 (<0.05), mengindikasikan jika Ho ditolak dan bisa diartikan jika terdapat hubungan tingkatan pengetahuan perawat tentang Australian Triage Scale terhadap response time pasien. Simpulan: Tingkat pengetahuan perawat mengenai Australian Triage Scale termasuk dalam kategori cukup. Sementara response time termasuk dalam kategori cepat. Hasil uji statistik Spearman’s Rank didapat nilai signifikansi (p-value) 0.002, sehingga terdapat hubungan yang signifikan antara tingkat pengetahuan perawat tentang Australian Triage Scale terhadap response time pasien.    Kata Kunci: Australian Triage Scale; Instalasi Gawat Darurat; Pengetahuan; Perawat; Response Time.